Development of An Educational Alphabet Game for Early Childhood Using Construct 3 - Praditya, Dinar Okto; Auliana, Sigit; Permana, Basuki Rakhim Setya (PT ARRUS Intelektual Indonesia, 2025)
The shift in learning behavior among Generation Z and millennial children, born into the digital era, emphasizes the need for engaging, interactive, and meaningful educational tools. This study aims to develop an Android-based educational game application using Construct 3 to help early childhood learners recognize and spell alphabets. The development follows the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation phases. The game incorporates drag-and-drop mechanics to arrange letters into words based on visual prompts. Black-box testing confirmed the application functioned as intended. The game is expected to enhance early literacy by providing a fun, interactive learning experience on mobile platforms.